Implementation of Zonation Policy and Their Impact on Income of Bajo Fishers in Mola, Wakatobi Regency - Surni Surni; Arusani Arusani; Ridwan Hasan (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2022)
The objectives of this study are as follows: (1) to analyze the implementation of the Wakatobi Regency National Park Zoning Policy, (2) to analyze the impact of Wakatobi National Park zoning on the income of Bajo fishermen in Mola, Wakatobi Regency. The method used in this research is a quantitative approach which is supported by qualitative data. The quantitative approach used is by surveying, listing and distributing questionnaires to the Wakatob District National Park Office and to Bajo fishermen in Mola who catch fish in the Tourism zone in Kapota Coral and Marine Protection zone in Karang Kaledupa and local use zones in the deep sea then take sample from one population. The results of this study are that the implementation of zoning policies has not been maximally implemented by both the management in this case the Wakatobi National Park and the Wakatobi Regency Government as well as by the fishing community who utilize the marine resources of the Wakatobi archipelago, this is evidenced by the continued use of the Kaledupa reef marine protection zone and the tourism zone.